All In! Designing Inclusive Meeting Spaces - Estvall, Camilla; Seidenfus, Marie (My University, 2020)
The current urban development in Gothenburg prioritises the needs and aesthetics of middle- and upper-class inhabitants (Thörn & Holgersson 2016, p.670, 681). This choice creates a city that excludes a big part of the population and denies them access to both housing and public spaces. Systematic gentrification and segregation lead on to ghettoisation and rising polarisation. A vicious circle starts that increases racism and conflicts in the society. The research hypothesis is that cultural differences and friction can be mitigated through inclusive meeting spaces that encourage interaction and cultural exchange. The thesis is an investigation about the development processes, design and impact of inclusive meeting spaces. The research is based on qualitative research methods such as interviews, site visits and literature studies. Urban theories, knowledge from practices and reference projects are combined into a design toolbox. Placemaking and Commoning are discussed as two possible approaches to achieve inclusive spaces. These ideas and the toolbox are illustrated on two sites in Brämaregården, Gothenburg. The main take-out of the research is that inclusive meeting spaces require both inclusive design elements and an inclusive process. Basic conditions for functional spaces are that they are safe, accessible and provide a reason to go there. Inclusive meeting spaces that include design elements that are appealing for diverse cultures and promote interaction are the foundation for cultural exchange. The more people are included in the development process, the more likely they develop a sense of ownership and feel like they belong to the space. Placemaking is a tool to create inclusive public spaces; however, the initiator uses the community to get input but does not share the responsibility. Commoning is hard to kickstart, but the approach stands for equal power distribution and is an alternative to the current state of urban planning. Developing inclusive meeting spaces is an essential part of achieving an inclusive city.
Keywords: common space, public space, meeting space, social sustainability, inclusive design